Awareness of COVID-19 and perception of work satisfaction among healthcare workers at Patan Hospital, Nepal - Acharya, Samita; Maharjan, Kripa; Dongol, Deveshree; Ghimire, Anupam (Journal of Patan Academy of Health Sciences, 2020)
Introduction: Healthcare workers (HCWs) awareness of disease outbreak, and working efficiently in a changed environment is vital to fight pandemic. How an institution responds to the crisis depends on HCWs response. This study aims to find out awareness of COVID-19 and work satisfaction of HCWs at Patan Hospital (PH), Nepal. Method: A cross-sectional questionnaires base descriptive study was conducted at PH, Patan Academy of Health Sciences, Nepal, in April 2020. The HCWs were grouped in to technical staff, doctors, and support staff. There were 20 questions each in the awareness of COVID-19 and work satisfaction domain. Ethical approval was obtained. Result: Of all the staff, 223 various level staffs responded to the questionnaire. There were 80 (35.9%) technical staff, 77 (34.5%) doctors and 66 (29.6%) support staff in the study. In the technical staff group 1106 (69.2%) responses were in favour of having good awareness and 1337 (83.5%) responses were in favour of satisfaction. In the doctors’ group 1233 (80.1%) responses were in favour of having good awareness and 1000 (65%) responses were in favour of satisfaction. In the support staff group 236 (17.7%) responses were in favour of having good awareness and 347 (26.2%) responses were in favour of satisfaction. Conclusion: Our study showed that technical staff and doctors had higher levels of perception of work satisfaction and awareness for COVID-19.